Relationship of Behavioral Factors with Existence of Aedes Aegypti in Buffer Area of Tanjung Intan Cilacap Port 2018 - Akhmad Purnianto; Retno Hestiningsih; Nissa Kusariana (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2019)
Background :DHF cases in the buffer area of Tanjung Intan Cilacap port is still high. Incident Rate (IR) reaches 0.54 per 1000 population. Density of DHF vectors is still abovethe required, HI 23.3%. The presence of Aedes aegypti larvae is influenced by several factors, one of which is behavior factor. This study aims to determine the relationship of behavior factors with the presence of larvae Ae. aegypti in buffer area of Tanjung Intan Cilacap Port.Methods: This is an observational analytical study with cross sectional design. The sample was chosen multistage sampling with 385 houses. This research uses data collection method through observation and interview. The study was conducted from May to June 2018. Results: The study yielded the following data. HI (28.1%), CI (26.13%), BI (37.9%). The chi-square analysis showed that variables related to the presence of larvae Ae. aegypti is Knowledge (p = 0,005), Attitude (p = 0,010) and Action (p = 0,039).Conclusion: Increased knowledge is needed to support the success of mosquito nest eradication programs (PSN).